Analytics and Intuition in the Process of Selecting Talent A Holistic Approach - Deters, Jürgen (De Gruyter, 2022)
In management, decisions are expected to be based on rational analytics rather than intuition. But intuition, as a human evolutionary achievement, offers wisdom that, despite all the advances in rational analytics and AI, should be used constructively when recruiting and winning personnel. Integrating these inner experiential competencies with rational-analytical procedures leads to smart recruiting decisions.